The effect of EDM die-sinking parameters on surface integrity for aluminium composite using copper electrode - Suraya, Laily; Mohd Amran, Md Ali; Nur Izan Syahriah, Hussein; Muhamad, Mohd Razali; RAJA ABDULLAH, RAJA IZAMSHAH; Taufik, Roni Sahroni (2014)
This paper investigates the performance of copper electrode on the surface integrity of aluminium alloy LM6 (Al-Sil2) in the electrical discharge machine (EDM) die sinking.The relationship between the machining parameters which is pulse-on time, pulse-off time, peak current and voltage on surface integrity was study.Copper tool of diameter 10mm was chosen as an electrode. Scanning electrone microscope (SEM) was used to observe the microstructure of LM6 after machining process and the average of recast layer (RL). It is found that the current and pulse on time was significantly affected the recast layer while pulse off time and voltage are less significant factor that affected the responses. Result shows that increasing the pulse duration has increased the recast layer.Thus, it shows that copper having capability to cut aluminium alloy LM6